L‐Carnitine protects against 1, 4‐benzoquinone‐induced apoptosis and DNA damage by suppressing oxidative stress and promoting fatty acid oxidation in K562 cells. Issue 10 (1st June 2020) - Sun, Rongli; Man, Zhaodi; Ji, Jiahui; Ji, Shuangbin; Xu, Kai; Pu, Yunqiu; Yu, Linling; Zhang, Juan; Yin, Lihong; Pu, Yuepu
Abstract: Widespread occupational and environmental exposure to benzene is unavoidable and poses a public health threat. Studies of potential interventions to prevent or relieve benzene toxicity are, thus, essential. Research has shown l ‐carnitine (LC) has beneficial effects against various pathological processes and diseases. LC possesses antioxidant activities and participates in fatty acid oxidation (FAO). In this study, we investigated whether 1, 4‐benzoquinone (1, 4‐BQ) affects LC levels and the FAO pathway, as well as analyzed the influence of LC on the cytotoxic effects of 1, 4‐BQ. We found that 1, 4‐BQ significantly decreased LC levels and downregulated Cpt1a, Cpt2, Crat, Hadha, Acaa2, and Acadvl mRNA expression in K562 cells. Subsequent assays confirmed that 1, 4‐BQ decreased cell viability and increased apoptosis and caspase‐3, ‐8, and ‐9 activities. It also induced obvious oxidative stress and DNA damage, including an increase in the levels of reactive oxygen species and malondialdehyde, tail DNA%, and olive tail moment. Additionally, the mitochondrial membrane potential was significantly reduced. Cotreatment with LC (500 μmol/L) relieved these alterations by reducing oxidative stress and increasing the protein expression levels of Cpt1a and Hadha, particularly in the 20 μmol/L 1, 4‐BQ group. Thus, our results demonstrate that 1, 4‐BQ causes cytotoxicity, reduces LC levels, and downregulates the FAO genes. In contrast, LC exhibits protective effects against 1, 4‐BQ‐induced apoptosis and DNA damage by decreasing oxidative stress and promoting the FAO pathway.